PENGARUH KADAR AIR TERHADAP NILAI KONSOLIDASI DI TANAH LEMPUNG PADA LOKASI YANG SAMA - Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Soil type is the most important known and understood by experts in civil engineering before designing or designing a construction thereon. Construction of such buildings before determining the type of foundation of the civil engineers must know beforehand what type of soil in the location that will be built with soil investigation to determine the physical properties and mechanical ground, so knowing how much water content, soil type what is in the location for facilitate the calculation of construction and also to determine how much length reduction / settlement. Tests carried out on site and soil type laboratory to determine moisture content, soil type and value of consolidation via tail test equipment consolidation test.